MISTURA DE ÃCIDO PIROLENHOSO COM GLIFOSATO NO CONTROLE DE Cynodon dactylon (L.) Pers. - Guiraldo, Nivaldo; Ambrosano, Edmilson JosÃ©; ArÃ©valo, Roberto Antonio; Mendes, Paulo Cesar Doimo; Rossi, Fabricio (REVISTA DE AGRICULTURA, 2015)
MISTURA DE ÃCIDO PIROLENHOSO COM GLIFOSATO NO CONTROLE DE Cynodon dactylon (L.) Pers.